Benthic foraminifera in the Nakdong River Delta (southeast Korea) and their response to middle Holocene climatic change in the coastal environment of the East Asian margin. (15th August 2022) - Takata, Hiroyuki; Irino, Tomohisa; Katsuki, Kota; Woo, Han Jun; Lee, Jun-Ho; Lim, Hyoun Soo; Ha, Sangbeom; Khim, Boo-Keun
Highlights: Benthic foraminifera in the NRD contain the Marine, Bay, and Opportunistic taxa. Precipitation and resultant river discharge increased in Korean Peninsula at ∼ 4 ka. Two small maxima of low oxygen-resistant taxon represent the fluctuated TWC. Replacement of two species implies the enhanced East Asian winter monsoon at 4.6 ka. Abstract: Fossil benthic foraminifera from five cores in the Nakdong River Delta (southeast Korea) were investigated to reveal paleoenvironmental changes across the middle/late Holocene transition, particularly focusing on ∼4 ka climatic event. Based on multi-dimensional scaling, benthic foraminifera are divided into (1) Marine taxa, (2) Bay taxa, and (3) Opportunistic taxa. Planktonic/total (benthic and planktonic) foraminiferal ratio decreased abruptly during 4.6–3.3 ka, and Nonionella stella was found commonly across ∼4 ka in core ND-01 (intermediate site among the five cores). These results imply that the ∼4 ka climatic event led to the stratification of less saline epilimnetic water underlain by more saline oxygen-poor hypolimnetic water in the Nakdong River Delta. This indicates temporal increase in precipitation in the Nakdong River drainage, which can be attributed to the intensified rainfall with the second Changma peak, associated with typhoons toward the Korean Peninsula. The small twin maxima of N. stella across ∼4 ka in core ND-01 were similar to those of the total sulfur contents in both Yeja Bay (southern Korea) and Lake Togo-ike (southwestern Japan). Such similarity in the stratigraphic patterns among the remote locations can be explained by the small-scale sea-level variations with the fluctuation of the Tsushima Warm Current, in addition to changes in precipitation. The common species of Haynesina sp. A was replaced by Elphidium somaense after ∼4.6 ka, which is likely due to the shift of passive dispersal as a result of the enhanced East Asian winter monsoon and/or the change in the westerly jet path.